2015
DOI: 10.1016/j.molcel.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Stability Distinguishes Two Different Promoter Types at All Protein-Coding Genes in Yeast

Abstract: Previous studies indicate that eukaryotic promoters display a stereotypical chromatin landscape characterized by a well-positioned +1 nucleosome near the transcription start site and an upstream -1 nucleosome that together demarcate a nucleosome-free (or -depleted) region. Here we present evidence that there are two distinct types of promoters distinguished by the resistance of the -1 nucleosome to micrococcal nuclease digestion. These different architectures are characterized by two sequence motifs that are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
356
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(423 citation statements)
references
References 51 publications
49
356
3
Order By: Relevance
“…Results from yeast (Weiner et al 2010;Xi et al 2011;Kubik et al 2015), plants (Vera et al 2014), mouse (Lombraña et al 2013;Deng et al 2015;Iwafuchi-Doi et al 2016;Mieczkowski et al 2016), worm (Ooi et al 2010), and fly (Henikoff et al 2009; have identified highly labile nucleosomes in 5 ′ and 3 ′ "nucleosome-free" regions. In yeast, Xi et al (2011) observed that fragile nucleosomes were associated with H2A.Z-containing promoter nucleosomes, believed to be involved in stress response (Li et al 2005;Zhang et al 2005).…”
Section: Mnase-resistant Nucleosomes Tend To Be In Gene Bodies and Comentioning
confidence: 99%
See 3 more Smart Citations
“…Results from yeast (Weiner et al 2010;Xi et al 2011;Kubik et al 2015), plants (Vera et al 2014), mouse (Lombraña et al 2013;Deng et al 2015;Iwafuchi-Doi et al 2016;Mieczkowski et al 2016), worm (Ooi et al 2010), and fly (Henikoff et al 2009; have identified highly labile nucleosomes in 5 ′ and 3 ′ "nucleosome-free" regions. In yeast, Xi et al (2011) observed that fragile nucleosomes were associated with H2A.Z-containing promoter nucleosomes, believed to be involved in stress response (Li et al 2005;Zhang et al 2005).…”
Section: Mnase-resistant Nucleosomes Tend To Be In Gene Bodies and Comentioning
confidence: 99%
“…Studies in yeast, C. elegans, Drosophila, and maize have used salt profiling and different MNase concentrations to identify a positive correlation between promoter fragility and expression (Henikoff et al 2009;Ooi et al 2010;Vera et al 2014;Kubik et al 2015). However, Xi et al (2011) used the same approach and observed the opposite effect.…”
Section: Mnase-resistant Nucleosomes Tend To Be In Gene Bodies and Comentioning
confidence: 99%
See 2 more Smart Citations
“…GTFs are also connected to particularly fragile nucleosome promoter architectures (Xi et al, 2011), a connection recently examined (Kubik et al, 2015). Using this data, we computed the nucleosome landscape for the different gene classes (Methods).…”
Section: Resultsmentioning
confidence: 99%